PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TASPEN PERSERO SAMARINDA - Saifuddin, In'am - (EKONOMIA, 2019)
This study aims to determine the effect of Motivation and Job Satisfaction on Employee Performance at PT. Taspen Persero Samarinda.Hypothesis based on the formulation of the problem in research 1. Suspected there is a positive and significant influence between the Motivation and Job Satisfaction together to the Performance of employees at PT. Taspen Persero Samarinda, 2. Suspected there is a positive and significant influence between the Motivation of Employee Performance at PT. Taspen Persero Samarinda, 3. Suspected there is a positive and significant influence between Job Satisfaction on Employee Performance at PT. Taspen Persero Samarinda.From the result of hypothesis test, it is used f test (test together by comparing f count and f table with significant level 95% or a = 0,05% F value 6,783 and Ftable 3,354 then Ho is rejected and Ha accepted. that the motivation variable (X1) and job satisfaction variable (X2) together have positive and significant influence on employee performance (Y) at PT Taspen Persero Samarinda.Conclusion based on research result at PT. Taspen Persero Samarinda showed that the variables Motivation and Job Satisfaction together affect the Performance of employees at PT. Tapen Persero Samarinda, and partially variable Motivation and Job Satisfaction affect on Employee Performance at PT Taspen Persero Samarinda